PENENTUAN ONGKOS MATERIAL HANDLING DI PT XYZ MENGGUNAKAN METODE COMPUTERIZED RELATIVE ALLOCATION OF FACILITIES TECHNIQUE ( CRAFT ) - Putri, Stevanie Primisari; Ranzani, Cut Dherra Widya Sari; Sihombing, Abi Mael; Fauzi, Yusuf; Wulandari, Fadila Woro (LPPM Universitas Bina Bangsa, 2024)
The development of the increasingly competitive manufacturing industry requires efficiency in various operational aspects, particularly in production costs. One significant cost component is Material Handling Costs (MHC), which can account for 30-75% of total production costs. PT XYZ, engaged in the clamp manufacturing industry, faces challenges in optimizing material handling costs. This investigation employs the Computerized Relative Allocation of Facilities Technique (CRAFT) to analyze and optimize MHC. The analysis results indicate that the total MHC at PT XYZ amounts to Rp 20,786,000, with the largest contribution coming from the material transfer between the Assembly Department and Quality Control. The considerable transfer distance and high transfer frequency are the main factors influencing material handling costs. The CRAFT method provides a comprehensive overview of material flow and transfer costs, that can serve as a basis for future facility layout optimization.